Facies Analysis of Lower Awynat Wanin Formations in Murzuq Basin, SW of Libya - Mohamed, Khalid; Albaghdady, Alsharef; Abdullah, Mustafa; Abduallah, Said (Journal of Pure & Applied Sciences, 2018)
The Awynat Wanin Group crops out on the southern flank of the Al Gargaf Uplift in the Murzuq Basin. The group has already been described and subdivided into lower and upper parts in previous studies by several authors. However, as already known, the differentiation between both parts remains unclear, especially between the similar formations of the Lower Part of the Awynat Wanin Group in study area. The Lower Part of Awynat Wanin Group includes the Bir Al Qaser, the Idri and the Qutta Formations. Intensive field works were carried out and six detailed stratigraphic logs have been measured and described in the study area. Macro to Mesofacies analysis concepts were applied in order to identify, characterise and describe the different facies of each formation separately, and finally to compare and differentiate between these similar formations of Awynat Wanin Group by using facies analysis methods.  Based on lithological facies analysis and field relationships, the three investigated formations can be differentiated as following. The Bir Al Qaser Formation consists mainly of sandstone facies deposited unconformably up on the Lower Paleozoic lithostratigraphic units of the Al Hasawna, Mamuniyat and Tanozoft formations. These unconformities are found in study area and attributed to the tectonic events prior to the Middle Devonian Age. The Bir Al Qaser Formation overlies conformably by Idri Formation in study area.  The Idri Formation is characterized by yellow brittle sandstone facies and contains abundant large scale cross bedding structures, whereas the Qutta Formation is composed mainly of white colored quarttizic sandstone facies as well as  silty claystones facies,  with high portions of trace fossils in the lower part of it.